2021
DOI: 10.1097/md.0000000000026196
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of anastomotic leakage after laparoscopic rectal surgery using creactive protein

Abstract: At present, anterior resection of the rectum or transabdominal rectal resection is the most common surgical technique for rectal cancer. Laparoscopic techniques are popular, and the efficacy and safety of laparoscopic rectal surgery have been confirmed. However, postoperative anastomotic leakage is a common, severe complication that leads to high mortality. Thus, early diagnosis of anastomotic leakage is important for reducing clinical consequences. The aim of this study was to determine whether C-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…From the univariant analysis in this study, we found that CRP on POD 4 achieved optimal AUROC of 0.857 with a cutoff value of 159.5 (Figure 2). This result echoed afar with numerous researches recently [27][28][29][30][31] , suggesting that CRP was one of the most commonly used and widely verified clinical predictors for postoperative AL and other postoperative infections. Other variables presenting great potential include NLR on POD 4 (AUROC=0.802, cutoff value=10.55), minimum serum albumin during hospitalization (AUROC=0.7475, cutoff value=32.25) (Figure 2), which also indicated that poor overall immunonutritional internal environment may increase risk of postoperative AL.…”
Section: Discussionmentioning
confidence: 58%
“…From the univariant analysis in this study, we found that CRP on POD 4 achieved optimal AUROC of 0.857 with a cutoff value of 159.5 (Figure 2). This result echoed afar with numerous researches recently [27][28][29][30][31] , suggesting that CRP was one of the most commonly used and widely verified clinical predictors for postoperative AL and other postoperative infections. Other variables presenting great potential include NLR on POD 4 (AUROC=0.802, cutoff value=10.55), minimum serum albumin during hospitalization (AUROC=0.7475, cutoff value=32.25) (Figure 2), which also indicated that poor overall immunonutritional internal environment may increase risk of postoperative AL.…”
Section: Discussionmentioning
confidence: 58%
“…1. Fifteen studies (12)(13)(14)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) met the defined inclusion criteria and had adequate data to be included in the meta-analysis.…”
Section: Results Resultsmentioning
confidence: 99%
“…The lack of a clear understanding of the pathophysiology behind AL led to the diversification of the investigated potential biomarkers across broad categories such as those of inflammation, ischemia, and tissue repair [ 11 ]. Although none of the examined biomarkers proved to be the gold standard, CRP shows promising results in contemporary literature [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%